Plasminogen Activator Inhibitor-1 Is Involved in Impaired Bone Repair Associated with Diabetes in Female Mice - Mao, Li (Public Library of Science, 2014)
Previous studies suggest that fracture healing is impaired in diabetes; however, the underlying mechanism remains unclear. Here, we investigated the roles of plasminogen activator inhibitor-1 (PAI-1) in the impaired bone repair process by using streptozotocin (STZ)-induced diabetic female wild-type (PAI-1 (+/+)) and PAI-1-deficient (PAI-1 (−/−)) mice. Bone repair and the number of alkaline phosphatase (ALP)-positive cells at the site of a femoral bone damage were comparable in PAI-1 (+/+) and PAI-1 (−/−) mice without STZ treatment. Although the bone repair process was delayed by STZ treatment in PAI-1 (+/+) mice, this delayed bone repair was blunted in PAI-1 (−/−) mice. The reduction in the number of ALP-positive cells at the site of bone damage induced by STZ treatment was attenuated in PAI-1 (−/−) mice compared to PAI-1 (+/+) mice. On the other hand, PAI-1 deficiency increased the levels of ALP and type I collagen mRNA in female mice with or without STZ treatment, and the levels of Osterix and osteocalcin mRNA, suppressed by diabetic state in PAI-1 (+/+) mice, were partially protected in PAI-1 (−/−) mice. PAI-1 deficiency did not affect formation of the cartilage matrix and the levels of types II and X collagen and aggrecan mRNA suppressed by STZ treatment, although PAI-1 deficiency increased the expression of chondrogenic markers in mice without STZ treatment. The present study indicates that PAI-1 is involved in the impaired bone repair process induced by the diabetic state in part through a decrease in the number of ALP-positive cells.